Dasar Genetik Kelainan Kromosom pada Kasus Keguguran Berulang - AHRIYA DWI AFRIANA; HARYA NAROTTAMA; EVA DIAH SETIJOWATI; HERNI SUPRAPTI; RETNO DWI WULANDARI (Hang Tuah Medical Journal, 2026)
Abstract Recurrent miscarriage (RPL) is defined as the loss of two or more pregnancies before the 24th week of pregnancy. Various factors contribute to RPL, including genetic abnormalities such as chromosomal abnormality. This study aims to ascertain the genetic basis of RPL. This study was an observational descriptive study. Data were collected retrospectively from medical records of patients with RPL at the Medical Genetics Laboratory, Faculty of Medicine, Wijaya Kusuma University Surabaya, from 2014 to 2023. The study population consisted of patients with a history of two to three recurrent miscarriages, with the exception of patients with TORCH infection. The results showed that of the 41 patients who met the inclusion and exclusion criteria, comprise of 17 (89.4%) men and 20 (90.9%) women had normal karyotypes, while 2 (10.4%) men and 2 (9.09%) women showed abnormal karyotypes. The chromosomal abnormalities identified were reciprocal translocation between chromosome (6;13) and heteromorphism on chromosome 9. The results showed the importance of knowing the genetic basis of RPL as a basis for providing genetic counseling.